COLORS INFLUENCE SOCIETY: रंगो का समाज पर प्रभाव - Chauhan, Sadhana (International Journal of Research -GRANTHAALAYAH, 2014)
The relationship between nature and man has been the center of philosophy, art and literary discourse from the ancient end of contemplation to the present. Therefore, color is also not untouched by this. "When the first ray of sun falls on an object, then that object becomes colored. A color touches you in such a way that many dreams begin to awaken in your imagination. Sometimes a color fascinates you in such a way that you start living the verses of life in harmony with it. And sometimes a color in your memory keeps you cheerful. "1 picture is a way of expressing the human mind. In the periphery of Malwa, the aforesaid shilachitra are found in various forms in Bhima Betka. From the pieces found there, from the Gheru, the Hidemachi and the Magenich, it is known that the paintings made from them were made there. In the context of the pictures and the sensations, adornment, memory, mystery and the configurations made of them, the center of the creation of colors is targeted only in the direction of the rich creation of colors. Any painting is based on the foundation of the interrelation of colors. "3 प्रकृति और मनुष्य का रिश्ता चिंतन के प्राचीन छोर से वर्तमान तक दर्शन, कला और साहित्यिक विमर्श का केन्द्र रहा है। अतः रंग भी इस से अछूते नहीं है।’’सूरज की पहली किरण जब किसी वस्तु पर पड़ती है तब वह वस्तु रंगमय हो जाती है। कोई रंग आपको इस तरह छूता है कि आपकी कल्पना में कई ख्वाब जागने लगते हैं। कभी कोई रंग आपको इस तरह मोहित कर लेता है कि आप उसके साथ लय मिलाते हुए जीवन का छंद जीने लगते हैं। और कभी कोई रंग आपकी स्मृति में ठहर आपको प्रफुल्लित रखता है।’’1 चित्र मानवीय मन को अभिव्यक्त करने का एक जरिया है। ’’मालवा की परिधि में पूर्वोक्त शिलाचित्र भीम बेटका में विविध रुप में प्राप्त होते हैं। गेरु, हिड़मची और मेगेनीच के वहां से प्राप्त टुकड़ों से ज्ञात होता है कि उनसे निर्मित रंगो से वहां चित्र बनाये जाते थे।’’2 एक चित्रकृति अपने में समाहित सौंदर्य को रंगो से परिपूर्ण करती है। चित्रों के संदर्भ में और उनसे प्रकट होने वाली अनुभूति, श्रृंगारिकता, स्मृति, रहस्य और इन सब से निर्मित विन्यास के केन्द्र में रंगो की विपुल सृष्टि का समाहन ही लक्षित होता है। कोई भी चित्रकृति रंगों के अंतर्सम्बन्ध की बुनियाद पर आधारित है।’’3